Metode Komunikasi yang Ideal dalam Pendidikan Keluarga Menurut Al-Qur'an - Ahmad Zain Sarnoto (Andragogi: Jurnal Diklat Teknis Pendidikan dan Keagamaan, 2021)
[THE IDEAL METHOD OF COMMUNICATION IN FAMILY EDUCATION ACCORDING TO THE QUR'AN]. The ability tocommunicate in a family is very necessary because communication barriers in the family will affect the harmonization of the relationship between husband, wife, and children. Al-Qur'an as the holy book of Muslims not only contains the rules of procedure in worship but also contains elements of communication education in the family. The purpose of this study is to discuss the ideal method of communication in family education according to the Quran. The method used in this study is a qualitative method with an analytical approach, the data sources are obtained from literature in the books, journals, and other libraries. The findings of this study indicate that there are several forms of communication described in the Qur'an related to the communication method, namely the method of qaulan baliigha, qaulan maisuura, qaulan layyina, qaulan ma'rufa, qaulan kariima and qaulan sadiida, these communication terms provide a signal about how to good communication, in the context of family education, effective communication is part of the cultivation of moral and religious education, it can even influence social attitudes in the form of honesty, discipline, politeness, and other good behavior. The conclusion in this study is to avoid conflict in the family, an effective communication method is needed, and the Qur'an has given a signal how to build ideal communication in the family